2014
DOI: 10.1186/s13068-014-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

New dry technology of environmentally friendly biomass refinery: glucose yield and energy efficiency

Abstract: BackgroundToday, most of pretreatments used to convert biomass into biofuels are based on expensive chemical processes that not only do not keep the major components intact after separation, but also consume water and generate many effluents. However, dry fractionation technologies are an important step for future biomass biorefineries since they do not require chemicals and do not generate wastewater. Therefore, the aim of the present study was to evaluate the feasibility of using milling combined with an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Indeed, classical procedures for the recovery of such molecules are based solid-liquid extraction with organic (and sometimes toxic) solvents (Naczk and Shahidi, 2004;Stalikas, 2007;Pérez-Serradilla and Luque de Castro, 2011). However, these methods generally do not leave intact the other components of the raw materials, they are expensive in energy, reagents and solvents, and require the treatment of effluents (Barakat and Rouau, 2014). Consequently, various extraction techniques were studied for the separation of simple phenolic compounds from the different meals, including novel dry fractionation processes or solvents assisted extractions with hydro-alcoholic mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, classical procedures for the recovery of such molecules are based solid-liquid extraction with organic (and sometimes toxic) solvents (Naczk and Shahidi, 2004;Stalikas, 2007;Pérez-Serradilla and Luque de Castro, 2011). However, these methods generally do not leave intact the other components of the raw materials, they are expensive in energy, reagents and solvents, and require the treatment of effluents (Barakat and Rouau, 2014). Consequently, various extraction techniques were studied for the separation of simple phenolic compounds from the different meals, including novel dry fractionation processes or solvents assisted extractions with hydro-alcoholic mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ultrafine milling (UFM) coupled to tribo-electrostatic separation (tES) have emerged as eco-friendly technologies for plant and agro-resource material fractionation under dry conditions [18][19][20][21] . Electrostatic separation is significantly more energy efficient and is able to produce enriched fractions with retained (native) functionality.…”
Section: Introductionmentioning
confidence: 99%
“…[ 69 ] It is reported that particles smaller than 1 mm have high surface area and a significant influence on penetration of reaction media into the polysaccharides during the pretreatment of LC biomass, but particles smaller than 0.4 mm did not result in further improvement in sugar yield. [ 77,78 ]…”
Section: High Pressure and Subcritical Fluids Pretreatment Of Lignocementioning
confidence: 99%